Photoelectrochemical conversion of methane into value-added products - Mehmood, Adeel; Chae, Sang Youn; Park, Eun Duck (Catalysts, 2021)
Methane has been reported to be directly converted into value-added products through various methods. Among them, photoelectrochemical (PEC) methane conversion is considered an eco-friendly method because it utilizes solar light and is able to control the selectivity to different products by means of application of an external bias. Recently, some PEC methane conversion systems have been reported, but their performance efficiencies are relatively lower than those of other existing thermal, photocatalytic, and electrochemical systems. The detailed mechanism of methane activation is not clear at this stage. In this review, various catalytic materials and their roles in the reaction pathways are summarized and discussed. Furthermore, promising semiconductor materials, co-catalysts, and oxidants have also been proposed. Finally, direct and indirect pathways in the design of the PEC methane conversion system have been discussed.
Keywords: Formic acid; Methane activation; Methanol; Oxidation; Photoelectrochemical conversion